Pola Strategi Aktivitas Penambang Timah Ilegal di Desa Berang Kabupaten Bangka Barat - Sariputra, Martinus (Jurnal Studi Inovasi, 2024)
West Bangka is one of the districts in the Bangka Belitung Islands Province that produces the highest tin, in 2021-2022 with relatively high prices. The impact of illegal mining activities causes problems to the environment such as the formation of kolong, and damage to existing ecosystems. Illegal mining activities are rife in PT. Sawit Thep and Sinar Mas. The role of the state through the security forces is to regulate illegal tin mining, but the phenomena that occur in the field where the security forces want to regulate illegal mining activities in the oil palm plantation area in Berang Village also vary, ranging from the absence of mining activities, the alleged cooperation and involvement of local strongman, the leak of regulatory information that will be carried out by the security forces, and resistance efforts from mining actors. This research was conducted in Berang Village, Simpang Teritip District, West Bangka Regency, this research uses the local strongman theory proposed by (Migdal) in order to identify strategy patterns, and factors that influence the strategy patterns of illegal tin miners and their correlation to the involvement of local strongmen. Illegal mining activities are carried out by the community by means of individuals and groups, this activity also has the support of local strongmen who have influence on the activities of illegal tin miners who are considered as deking who provide direction to illegal tin mining actors. Miners carry out activities freely even though there are times when they carry out mining activities cat-and-cat. This is inseparable from the involvement of local strongmen.